2019
DOI: 10.1007/s11239-019-01922-w
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular dysfunction is superior and sufficient for risk stratification by a pulmonary embolism response team

Abstract: Introduction: Several risk stratification tools are available to predict short-term mortality in patients with acute pulmonary embolism (PE). The presence of ventricular (RV) dysfunction is an independent predictor of mortality and may be a more efficient way to stratify risk for patients assessed by a Pulmonary Embolism Response Team (PERT). Methods:We evaluated 571 patients presenting with acute PE, then stratified them by the Pulmonary Embolism Severity Index (PESI), by the BOVA score, or categorically as l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 34 publications
1
18
0
2
Order By: Relevance
“…Besides, in a retrospective analysis of confirmed PE patients presenting to the emergency department, the authors observed an underestimation of PE-related mortality using existing PE prognostic models. [ 42 ] Therefore, the utility of age or chronic cardiopulmonary disease in PE prognostic models may need further evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, in a retrospective analysis of confirmed PE patients presenting to the emergency department, the authors observed an underestimation of PE-related mortality using existing PE prognostic models. [ 42 ] Therefore, the utility of age or chronic cardiopulmonary disease in PE prognostic models may need further evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…PESI has been used for the risk stratification of right ventricular dysfunction and for prediction of short-term mortality after acute PE. 38,39 Therefore, there may be an alternative factor that attenuates the effect of OSA on the mortality and additional adverse outcomes. We speculate that one such potential mechanism could be a phenomenon termed ischemic preconditioning.…”
Section: Discussionmentioning
confidence: 99%
“…The right ventricular dysfunction on echocardiogram has an important role for prognosis as seen in different studies that show a correlation between adverse outcomes and right ventricular dysfunction in pulmonary embolism [ 22 ]. Although in our study we did not study the correlation of RV dysfunction with adverse outcomes, it can however be used to risk-stratify patients with acute PE [ 23 ].…”
Section: Discussionmentioning
confidence: 99%